task/29958638 решить уравнение √(x+6) +√(x-1) +2√(x²+5x -6) = 51 -2x
решение √(x+6) +√(x-1) +2√(x²+5x -6) = 51 -2x ⇔√(x+6) +√(x-1)+2√(x+6)(x-1) =51 -2x ОДЗ : { x+6 ≥ 0 ; x -1 ≥ 0. ⇔ { x ≥ - 6 ; x ≥ 1. ⇒ x ≥ 1 || иначе x ∈ [ 1 ; ∞) || На ОДЗ
√(x+6) +√(x-1)+2√(x+6)(x-1) =51-2x⇔√(x+6)+√(x-1)+2√(x+6)√(x-1)=51 -2x
замена: u=√(x+6) ≥0 ; v=√(x - 1) ≥0 ⇒ 51 -2x =56 - ( x +6 +x -1) = 56 - (u²+v²).
Получаем систему уравнений с переменными u и v :
{ u+v+2uv =56 - ( u² + v² ) ; u² - v² =7.⇔ { (u+v)²+( u + v )- 56 = 0 ; u² - v² =7.⇔
(u+v)²+ ( u + v )- 56 =0 ⇔ [ u+ v = - 8(посторонний) ; u+v=7.
{ u + v =7 ; u² - v² =7.⇔ { u + v =7 ; (u - v)(u+v) =7.⇔ ± { u + v =7 ; u - v = 1.⇔
[ u =4 ; v =3 . обратная замена: √(x+6) = 4 ⇒ x = 10 * * * или из √(x - 1) =3 * * *
ответ: 10 .